Commentary on Editorial “Towards an evidence based alcohol policy” - Rajasuriya, Mahesh (Sri Lanka College of Psychiatrists, 2012)
We received a detailed response on the editorial of the previous issue “Towards an evidence based alcohol policy”. Instead of publishing it as a Letter to the Editor, which would have limited the length of the response, we decided to publish it as a commentary. We have also invited the author of the editorial to respond to the commentary. Correspondence on this topic is now closed.
Keywords: Commentary; Editorial; alcohol policy